SIMPATIKA: Sistem Pemantauan Kelembaban Tanah dan Suhu Pada Budidaya Mangga di Desa Sumberjaya Karawang - Kurniawan, Teguh (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
Mango production in Sumberjaya Village has decreased, which has led to a decline in the income of the mango farming community. This research aims to help Sumberjaya Village farmers increase mango production by providing information on land suitability for effective cultivation. The designed system uses YL-69 soil moisture sensor and DHT22 temperature sensor to detect land environmental conditions. Tests were conducted on 3 different land areas, each with ten test points 6 meters apart according to the standard of mango seedling planting. Results show that the device is able to identify soil conditions in five categories: very dry, dry, moderately moist, moist, and wet. The “moist” category (61-80%) was identified as the optimal condition for planting mango seedlings. The ambient air temperature ranges from 24°C-30°C, suitable for mango cultivation. Variations in soil moisture even within one area are likely due to factors such as rainfall and differences in soil structure and texture. The tool is able to provide information to farmers regarding the condition of the land, enabling better decision-making in mango cultivation. With this simple design, it is hoped that this technology can continue to be developed to support the sustainability of agriculture in Sumberjaya Village and surrounding areas.